The Malay version of the attitudes and beliefs about cardiovascular disease (ABCD-M) risk questionnaire: a translation, reliability and validation study - Zarudin Mat Said; Tengku Alina Tengku Ismail; Anees Abdul Hamid; Ramesh Sahathevan; Zariah Abdul Aziz; Kamarul Imran Musa (BMC, 2022)
Abstract Background Cardiovascular disease (CVD) and stroke are global public health problems and cause high mortality, especially in low- and middle-income countries. Knowledge and awareness are critical points in managing the risk in the general population. The Attitudes and Beliefs about Cardiovascular Disease (ABCD) risk questionnaire was developed to evaluate the awareness of stroke and CVD risk. Thus, the government can set up a practical risk assessment and management programme. The initiative will encourage people to seek healthcare timely and reduce the possibilities of developing complications. Objective This study aimed to translate and validate the ABCD risk questionnaire into the Malay language and evaluate the psychometric properties of the Malay version in the general population in Malaysia. Methods The questionnaire was translated using a standard forward-backwards translation method. The validation was perfomed by both expert panels and a potential user group. Next, the exploratory factor analysis was conducted to examine factorial validity. The respondents were selected from the government health clinics and according to the study criteria irrespective of the CVD risk. We used Cronbach's alpha and Raykov's rho to explore the internal consistency and composite reliability of the 18 items from three domains. Finally, the confirmatory factor analysis (CFA) was conducted using a robust maximum likelihood estimator. Results The content and face validity indices were determined to be 0.94 and 0.99 respectively. Data were obtained from 179 respondents (mean age, 36.8 years; female, 68.2%; secondary level education, 51.1%). The internal consistency and composite reliability of the domains showed good results ranging from 0.643 to 0.885. The factor loadings of each item were acceptable (> 0.3), and the fit indices from the CFA resulted in a good model fit [χ2 (p-value = 0.16), SRMR = 0.054, RMSEA = 0.029, CFI = 0.99, TLI = 0.99)]. Conclusions The Malay version of the ABCD risk questionnaire is a valid and reliable tool to assess the awareness of stroke and CVD risk in the general population in Malaysia.